2002
DOI: 10.1007/s00442-002-0986-5
|View full text |Cite
|
Sign up to set email alerts
|

Sapling growth and survivorship as a function of light in a mesic forest of southeast Texas, USA

Abstract: For seven species in a mature mesic forest in southeast Texas, we estimated species-specific parameters representing radial growth in high light and low light for tree saplings. Shade-intolerant species had higher asymptotic growth rates and lower low-light growth than tolerant species. Inspection of species positions on graphs of low-light growth versus high-light growth suggested that there was a trade-off between these two processes across species. By linking functions of growth versus light and mortality v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 48 publications
4
62
1
Order By: Relevance
“…(1) following Drever and Lertzman (2001) and Lin et al (2002) the Michaelis-Menten function was applied in the case of relative PAR and (2) the Mitscherlich function was applied in all other factors, i.e. SW, IRI and ICI.…”
Section: Data Evaluationmentioning
confidence: 99%
“…(1) following Drever and Lertzman (2001) and Lin et al (2002) the Michaelis-Menten function was applied in the case of relative PAR and (2) the Mitscherlich function was applied in all other factors, i.e. SW, IRI and ICI.…”
Section: Data Evaluationmentioning
confidence: 99%
“…Because M A changes faster in shade-intolerant species, RGR is also likely to change faster, leading to RGR rank changes among woody species of contrasting shade tolerance (Sack & Grubb 2001. Few studies have investigated the growth rates of established saplings (Pacala et al 1994;DeLucia et al 1998;Niinemets 1998;Lin et al 2002), and even fewer studies have investigated both the above-and below-ground plant biomass pools (DeLucia et al 1998;Niinemets 1998;Claveau et al 2005). Nevertheless, the growth rate vs. long-term irradiance response curves developed simultaneously for seven to ten species of contrasting shade tolerance, demonstrate an overall positive correlation between plant growth potential in low light and species shade tolerance rank with only a few exceptions (Pacala et al 1994;Lin et al 2002).…”
Section: Complex Interactions Between Seed Size and Relative Vs Absomentioning
confidence: 99%
“…Pacala et al (1994Pacala et al ( , 1996 challenged the traditional paradigm of shade tolerance by proposing that a tradeoff between growth in high light and survivorship in low light is more important than a generally believed high-light growth vs low-light growth tradeoff (see Lin et al 2002 and references therein). Our results in a mesic forest suggested that it may not be appropriate to think of these two tradeoffs as one opposed to another and that the importance of growth and survivorship as components of shade tolerance may be system-specific (Lin et al 2002).…”
Section: Introductionmentioning
confidence: 97%